2016
DOI: 10.1016/j.ajic.2016.04.214
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in intensive care: The impact of bacteremia and the utility of systemic inflammatory response syndrome

Abstract: Mortality in intensive care: The impact of bacteremia and the utility of systemic inflammatory response syndrome. American Journal of Infection Control, 44(11), pp. 1291Control, 44(11), pp. -1295Control, 44(11), pp. . (doi:10.1016Control, 44(11), pp. /j.ajic.2016 This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it. TitleMortality in intensive care -the impact of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…characteristics and outcomes of severe sepsis patients with and without bacteremia. Several studies have reported on the epidemiology of bacteremia and sepsis, although the quality of such studies is varied 5,9,10,[14][15][16][17] . In the present study, higher rates of septic shock were seen in patients with versus without bacteremia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…characteristics and outcomes of severe sepsis patients with and without bacteremia. Several studies have reported on the epidemiology of bacteremia and sepsis, although the quality of such studies is varied 5,9,10,[14][15][16][17] . In the present study, higher rates of septic shock were seen in patients with versus without bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…However, in-hospital mortality was not significantly different between patients with and without bacteremia in our study. Previous studies have reported various mortality rates in patients with bacteremia [6][7][8]10,15 . The diversity of the study population, setting, and study design may have contributed to the different impacts of bacteremia, which may have been influenced by the proportion of patients with each pathogenic species in each study 5,14 , or evidence of pathogen may have aided in selecting the appropriate antibiotic 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Length of stay and mortality were found to be increased in ICU patients with bacteremia. [ 21 ] In a study conducted in a tertiary ICU, bacteremia was an independent risk factor for nosocomial infection-related mortality. [ 22 ] According to our study results, overall mortality was not significantly different between bacteremic and nonbacteremic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Yet complementary studies are necessary to identify specific patient-groups for whom molecular testing results could majorly improve clinical outcome. The intensive care unit (ICU) copes with a BSI prevalence of 7.8% and an associated mortality rate of 30–40% [89]. Calculated as the third most common infection, ICU-BSIs moreover lead to extended length of stay and major hospital costs [1011].…”
Section: Introductionmentioning
confidence: 99%